Selection of Macrocybe crassa mushroom for commercial production - Inyod, Tanapak; Sassanarakit, Suriya; Payapanon, Achara; Keawsompong, Suttipun (Agriculture and Natural Resources, 2016)
Macrocybe crassa or Tricholoma crassum (Berk.) Sacc. (synonym) is a wild, edible mushroom in Thailand. This mushroom has a large fruiting body with meaty texture and a delicious taste. However, this mushroom is not commercially cultivated at a large scale. In this study, five strains of M. crassadDOA, DOA-1, DOA-4, DOA-7 and DOA-10dwere cultivated on a ratio of rubber tree sawdust to fine rice bran to magnesium sulfate (MgSO4.7H2O) to calcium oxide (CaO) of 100:3:0.2:1 (weight per weight). Their growth, productivity and characteristics of the fruiting body were investigated. The results revealed that DOA-10 gave the highest yield (215.10 g per 0.6 kg of substrate) with 59.26% biological efficiency. Observation showed that its pileus diameter, stalk diameter and stalk length were 6.78 cm, 2.75 cm and 13.54 cm, respectively. The dried samples of DOA-10 contained protein, carbohydrates, ash and fat at 13.71%, 68.08%, 12.06% and 2.49% respectively. Moreover, they contained high contents of both macronutrients and micronutrients: potassium (43,100 mg/kg), calcium (492.00 mg/kg), magnesium (1046.66 mg/kg), sodium (936.33 mg/kg), iron (283.21 mg/kg), zinc (53.79 mg/kg) and manganese (17.55 mg/kg). These results confirmed that DOA-10 is a promising strain for commercial cultivation.